Employee Performance in Jakarta Banks: The Role of Training, Compensation, and Integrity - Niken Rosiana; Didin Hikmah Perkasa (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2026)
This study is motivated by the dynamics of the banking world continue to evolve rapidly, particularly in Jakarta City with the cultural diversity of high-end urban lifestyle. The research examines the influence of Training, Compensation, and Integrity on Employee Performance in Jakarta Banks. This study applies a quantitative approach with an associative design and distributing questionnaires to 187 Employee respondents residing in Jakarta. Data were analyzed with Partial Least Squares Structural Equation Modelling (PLS-SEM) through Smart PLS 4.0 software through Outer Model (validity, reliability, and Fornell-Larcker criterion) and Inner Model analysis. The results show compensation and integrity have a significant effect on employee performance, except training did not significant impact. Among the two, integrity emerged as the most dominant factor. These findings underscore the importance of incentive-based compensation and shaping morality and professional integrity to manage their motivation and commitment as strategic efforts to boost their performance in the banking sector. Yet, perceive training as irrelevant and already skilled based on background and length of service.